2015
DOI: 10.1002/chem.201501882
|View full text |Cite
|
Sign up to set email alerts
|

Cyclometalated Iridium(III) Complexes as Two‐Photon Phosphorescent Probes for Specific Mitochondrial Dynamics Tracking in Living Cells

Abstract: Five cyclometalated iridium(III) complexes with 2-phenylimidazo[4,5-f][1,10]phenanthroline derivatives (IrL1-IrL5) were synthesized and developed to image and track mitochondria in living cells under two-photon (750 nm) excitation, with two-photon absorption cross-sections of 48.8-65.5 GM at 750 nm. Confocal microscopy and inductive coupled plasma-mass spectrometry (ICP-MS) demonstrated that these complexes selectively accumulate in mitochondria within 5 min, without needing additional reagents for membrane pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 68 publications
(49 citation statements)
references
References 76 publications
2
46
1
Order By: Relevance
“…The structure shows a hydroxy-group and a mes-ring attached to C3 of the Boc-protected piperidine and is consistent with the NMR, mass-spectrometry and elemental analyses. The rings in the cation [7] are also almost perpendicular to the torsion angle (C4-C3-C6-C7) of 72.98 (17)°. 2) shows that the tertiary hydroxy-group in 3 has been dehydrated to form an alkene bond between C3 and C4, and the corresponding bond length is 1.392(2) Å.…”
Section: Molecular Structuresmentioning
confidence: 96%
See 1 more Smart Citation
“…The structure shows a hydroxy-group and a mes-ring attached to C3 of the Boc-protected piperidine and is consistent with the NMR, mass-spectrometry and elemental analyses. The rings in the cation [7] are also almost perpendicular to the torsion angle (C4-C3-C6-C7) of 72.98 (17)°. 2) shows that the tertiary hydroxy-group in 3 has been dehydrated to form an alkene bond between C3 and C4, and the corresponding bond length is 1.392(2) Å.…”
Section: Molecular Structuresmentioning
confidence: 96%
“…Significantly, this allows for the harvesting of both singlet and triplet excitons within an OLED, theoretically allowing 100% internal quantum, and since their first deployment in these devices by Forrest et al, they have been the subject of numerous patents and papers. [12][13][14][15][16][17][18][19][20][21] Their emission spectra can be readily tuned by altering either the ancillary or 2-phenylpyridine ( ppy) ligand. [12][13][14][15][16][17][18][19][20][21] Their emission spectra can be readily tuned by altering either the ancillary or 2-phenylpyridine ( ppy) ligand.…”
Section: Introductionmentioning
confidence: 99%
“…In this way, the charge-transfer property and the extended π-conjugation over the whole molecule results in good TPA properties of 5 compared to the previously reported complexes of similar structures. Besides, it is worth pointing out that some iridium(III) complexes bearing two cyclometallated unsubstituted 2-phenylpyridines and a 2-phenylimidazo[4,5-f] [1,10]phenanthroline, characterized by two-photon absorption crosssections in the range 48.8-65.5 GM at 750 nm, were utilized as efficient agents for mitochondrial imaging and tracking in living cells under two-photon (750 nm) excitation [21].…”
Section: Resultsmentioning
confidence: 99%
“…reported seven new Ir (III) complexes 57–63 having imidazole and phenanthroline moiety to have mitochondrial image . The same research group also reported few more complexes 64–68 for mitochondrial imaging in living cell . (Scheme A‐4C).…”
Section: Compartmentalization and Staining Of Cellsmentioning
confidence: 99%